Hypertrophy signaling, muscle growth and increases in strength after blood flow restricted resistance exercise - Bjørnsen, T.; Dalen, T.; Løvstad, A.; Paulsen, G.; Wernbom, M.; Flesche, A.; Berntsen, S.; Uglestad, I.; Østgaard, H.; Raastad, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: High frequency blood flow restricted resistance exercise (BFRRE) has been shown to induce rapid muscle growth accompanied by increased numbers of satellite cells and myonuclei (1). However, the intracellular signaling behind the hypertrophic response is still largely unknown and notably, the hypertrophy plateaued after the first week of high frequency BFRRE (1). Therefore, the present study aimed to investigate the anabolic signaling pathways, muscle growth and maximal strength during and after two blocks of high frequency BFRRE interspersed by 10 days of rest. Methods: Ten young men and women (22-28 yrs) completed two blocks of seven BFRRE sessions in five days, separated by 10-days of rest. The exercise protocol consisted of four sets with unilateral knee-extension to voluntary failure (30 s rest between sets) at 20 % of one repetition maximum (1RM). Both legs were exercised, and the pressure cuff was inflated to 90-100 mmHg. Seven biopsies were obtained from m. vastus lateralis; "acute" biopsies were collected 1 h after the first bout of each training week. Phosphorylation levels of eukaryotic translation elongation factor 2 (eEF2), p70S6 kinase (p70) and p38 mitrogen-activated prtein kinases (p38) were measured using western blotting. Muscle growth was assessed as changes in muscle fiber area (MFA) using immunohistochemistry, as well as thickness of m. vastus lateralis and cross sectional area (CSA) of m. rectus femoris applying ultrasound imaging. Strength was measured as 1RM in knee extension. Results: Phosphorylation (p-) levels of p70 and p38 were significantly higher in the acute biopsies from the first training week compared to baseline (p=0.02 and p=0.04, respectively). There was a tendency to higher levels of p-p70 and p-p38 in the acute biopsies of the second training week (p=0.07 and p=0.10, respectively). No changes were observed in p-eEF2. CSA of m. rectus femoris and muscle thickness of m. vastus lateralis were significantly greater 10 days after BFRRE (mean±SD, 7±4%; p<0.001 and 6±3%; p<0.001, respectively). The MFA of type 1 and 2 fibers showed non-significant trends towards increases; 19±23 % (p=0.06) and 15±27 % (p=0.20), respectively. 1RM in knee extension increased with 6±7 % (p=0.03). Discussion: Two blocks of high frequency BFRRE, interspersed by 10 days of rest, produced gains in muscle thickness, CSA and maximal strength. Furthermore, BFRRE activates intracellular signaling pathways associated with training-induced muscle hypertrophy, and the trained muscle seems to retain its responsiveness to the training stimulus when 10 days of rest intersperse high frequency training blocks.